2020
DOI: 10.21037/cdt.2019.10.03
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of inherited cardiomyopathies in Africa

Abstract: With increased globalisation and modernisation, different regions are becoming progressively more interconnected through the movement of people, goods, capital and ideas. The health systems in sub-Saharan Africa (SSA) (Table S1) are consequently facing challenges imposed by a unique quadruple burden of increasing noncommunicable diseases (NCDs), persisting morbidity and mortality from communicable diseases, high maternal and infant mortality, and trauma and interpersonal violence (1-3). Combine these factors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 180 publications
0
6
0
Order By: Relevance
“…Correlating genetic information with phenotypic presentation and disease outcome could have profound implications on patient management and should be explored further. This is particularly true in African populations, where the risk of PPCM is higher [ 4 , 84 ], the prognosis is poorer [ 85 ], and the knowledge of cardiomyopathy genetics is scarce [ 86 ]. PPCM has a broader aetiology than other forms of heritable cardiomyopathy, and further research is needed into the role of additional genes such as those involved in (auto)immunity, angiogenesis, metabolism, and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Correlating genetic information with phenotypic presentation and disease outcome could have profound implications on patient management and should be explored further. This is particularly true in African populations, where the risk of PPCM is higher [ 4 , 84 ], the prognosis is poorer [ 85 ], and the knowledge of cardiomyopathy genetics is scarce [ 86 ]. PPCM has a broader aetiology than other forms of heritable cardiomyopathy, and further research is needed into the role of additional genes such as those involved in (auto)immunity, angiogenesis, metabolism, and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a review by Shaboodien et al the authors looked for all studies discussing the genetics of inherited cardiomyopathies in Africa and only found four studies on ACM, one on RCM, and none on LVNC. 75 Furthermore, racial disparities may not solely originate from pathogenic mutations themselves but extend to the clinical expression of the disease, influenced by both intrinsic (biological) and extrinsic factors, such as disparities in socioeconomic status or discriminatory practices within health care systems, as previously elucidated. 76 77 Unfortunately, many patients do not receive genetic testing and would not receive genetic-specific management.…”
Section: Exploring Disparities In Cardiomyopathy From Clinical Practi...mentioning
confidence: 99%
“…Nevertheless, in SSA studies on genetics of cardiomyopathies, including DCM is limited to southern region specifically South Africa, while in other parts of SSA its diagnosis is based on laboratory findings and imaging techniques with limited access [32,33]. Shaboodien et al, in a review on genetics of inherited cardiomyopathies in Africa, identified only nine studies in DCM, of which seven were conducted in South Africa, while the other two were from Tunisia and Egypt [34]. A study done in South Africa by Ntusi et al, which looked into clinical characteristics and outcomes of familial and idiopathic DCM in 109 patients, noted that the majority of the study population were young, with male predominance, and clinicaly presented with HF by New York Heart Association(NYHA) class III-IV [35].…”
Section: Idiopathic Dcm In Hf Patients In Ssamentioning
confidence: 99%